2009
DOI: 10.1111/j.1365-2699.2009.02086.x
|View full text |Cite
|
Sign up to set email alerts
|

Potential impacts of climatic change on the breeding and non‐breeding ranges and migration distance of EuropeanSylviawarblers

Abstract: Aim To explore the potential impacts of climatic change on species with different migratory strategies using Sylvia warblers breeding in Europe as a 'model' species group.Location Europe and Africa.Methods Climate response surfaces and generalized additive models (GAMs) were used to model relationships between species recorded breeding and nonbreeding ranges and recent climate. Species potential future breeding and nonbreeding ranges were simulated for three scenarios of late 21st-century climate. The simulate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
79
0
6

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(89 citation statements)
references
References 68 publications
4
79
0
6
Order By: Relevance
“…In populations where large areas of unsuitable habitat are located between current breeding and wintering areas a gradual shortening of migration distance may not be possible (29,57). Habitat loss in current winter ranges of many long-distance migrants, which is predicted to increase with global warming, will worsen this situation, because it will cause an increase in migration distance (45,58) and prevent adaptation. Moreover, high rates of evolutionary change, as found here for the amount of migratory activity in the blackcap, increase the risk of extinction and may not be sustained for a longer period (59).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In populations where large areas of unsuitable habitat are located between current breeding and wintering areas a gradual shortening of migration distance may not be possible (29,57). Habitat loss in current winter ranges of many long-distance migrants, which is predicted to increase with global warming, will worsen this situation, because it will cause an increase in migration distance (45,58) and prevent adaptation. Moreover, high rates of evolutionary change, as found here for the amount of migratory activity in the blackcap, increase the risk of extinction and may not be sustained for a longer period (59).…”
Section: Discussionmentioning
confidence: 99%
“…Here we test whether blackcaps have adapted migratory behavior to the recent increase in ambient temperature and to the resultant widening of the reproductive time window (42)(43)(44). Specifically, we predicted a shortening of migration distance and a delay in departure from the breeding grounds as a response to the global increase in temperature (45,46).This study aims at unraveling the mechanisms underlying adaptation of migratory birds to climate change by continuously monitoring migratory behavior, and the effects causing its variation, using a combination of a long-term common garden experiment in time and selective breeding in captivity under a rigidly controlled environment. We demonstrate that there has been a strong evolutionary reduction in migratory activity and that this process will result in the rapid evolution of residency in an exclusively migratory bird population.…”
mentioning
confidence: 99%
“…Average model projections for the migration rates that would be necessary to track climate change in Europe are substantially larger than those historically observed, but the magnitude of the mismatch depends heavily on the climate change scenario Huntley et al 2008;Doswald et al 2009). Simulations with bioclimate envelope models suggest large local (per grid cell) species losses and turnover rates, assuming that species fully track climate change by migration (Thuiller et al 2005;Pompe et al 2008).…”
Section: Range Shifts and Biodiversitymentioning
confidence: 97%
“…We do not envisage that modeling climate effects on winter habitats of birds will be possible in the near future. On a coarse resolution, Doswald et al (2009) explored the potential impacts of climatic change on breeding and wintering ranges of Sylvia warblers. They showed that migratory species can be expected to suffer greater negative impacts from climate change than resident species because migration distances can substantially increase owing to climate change.…”
Section: Predicted Population Changesmentioning
confidence: 99%